Implementing Duolingo as A Supplementary Tool For Vocabulary and Pronunciation Mastery - Leini Nadira Rambe; Yuliarti Yuliarti; Besse Puspitha Syarif; Muhammad Ali Ode (Universitas Nurul Jadid, 2026)
This study examines the implementation of Duolingo as a supplementary tool for vocabulary and pronunciation mastery among second-year university students taking English subjects. The study was conducted in response to the challenges often found in traditional classroom learning, particularly in maintaining student motivation and helping learners retain new vocabulary over time. Using a qualitative method with simple quantitative measurement, the research combined questionnaire results and semi-structured interviews to understand students’ experiences in using the application. The findings show that Duolingo was generally helpful and well received by the students. Most of participants agreed that the application helped them learn new English vocabulary, while three-fourths of them stated that it increased their confidence in pronunciation. These results indicate that Duolingo functioned effectively as a complementary learning medium that supported classroom instruction. The integration of clear audio features, vivid visual cues, and interactive tasks facilitated a flexible learning environment that catered to diverse student needs. Its visual and audio features, interactive tasks, and repeated exposure to language forms helped students practice English in a more engaging and flexible way. In addition, the gamified system encouraged regular use and made learning feel less stressful. Overall, the study suggests that Duolingo can be a useful supplementary tool for improving vocabulary and pronunciation while also promoting independent learning habits outside the classroom.